Pengaruh Perencanaan Pajak Terhadap Nilai Perusahaan dengan Kualitas Corporate Governance sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2012-2014) - Pandu Dewanata; Tarmizi Achmad (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the effect of the tax planning on firm value. Independent variables that used in this research is tax planning as measured by ETR ratio. While the dependent variable is firm value measure with Tobins’Q . This research is the development of research conducted by (Nanik Lestari, 2014) the differences are measurement of tax planning, firm value and samples that used. This study specifically illustrates the tax planning and its influence on firm value. The population in this study is taken from 200 manufacturing companies listed in Indonesia Stock Exchange during 2012 to 2014. The sampling method is using purposive sampling method and obtained sample of 67 manufacturing companies. The results of this study indicate that there is a positive correlation between tax planning that is proxied by ETR ratio and firm value proxied by Tobins’Q. Corporate governance as moderating variable strengthten the correlation between tax planning and firm value The implication stated that corporate governance affect manufacturing company which make the practice of tax planning legally becomes reason for management for increasing prosperity both firm and stakeholders